KOMPOSISI DALAM FOTOGRAFI - Yuliadewi, Lesie (Nirmana, 2000)
At the first time%2C Frederick Scott Archer found collodion%2C an element of photography%2C that covered the glasses and can be put it on obscura camera to have the picture. This methode has used before%2C in all European and American countries. The photographer%2C at that time%2C had not cared about the quality of the picture. Meanwhile together advanced technology%2C human discovered some elements that can make a picture became more sharply. From that point%2C photographers become more appreciate with photography work. All sorts of aspects that can give more value for the picture%2C has been more attractived%2C ie: composition that can help to discover a better quality of photography work. Abstract in Bahasa Indonesia : Pada mulanya Frederick Scott Archer menemukan collodion%2C bahan baku fotografi%2C yang dilapiskan ke kaca dan langsung dipasang pada kamera obscura untuk menghasilkan gambar. Cara ini digunakan untuk memotret di seluruh Eropa dan Amerika. Para fotografer pada zaman itu masih belum memperhatikan kualitas gambar. Namun%2C seiring dengan perkembangan zaman dan kecanggihan teknologi%2C manusia menemukan bahan yang dapat membuat sebuah gambar menjadi tajam%2C dan penggemar fotografi pun mulai memperhatikan nilai lebih karya fotografi. Berbagai aspek penunjang keberhasilan yang memberikan nilai lebih mulai diperhatikan%2C antara lain komposisi yang dapat membantu terwujudnya suatu karya fotografi yang bermutu. photography%2C composition